2010
DOI: 10.3390/s101009337
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Horizontal Penetrometer for Measuring On‑the‑Go Soil Resistance

Abstract: Soil compaction is one of the main negative factors that limits plant growth and crop yield. Therefore, it is important to determine the soil resistance level and map it for the field to find solutions for the negative effects of the compaction. Nowadays, high powered communication technology and computers help us on this issue within the approach of precision agriculture applications. This study is focused on the design of a penetrometer, which can make instantaneous soil resistance measurements in the soil h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…Cone penetrometers are recommended in the American Society of Agricultural Engineers (ASAE) Standards as a standard method for measuring the penetrometer resistance PR of soils [ 14 ]. They are extensively used to evaluate soil strength especially in agriculture for resistance to root penetration [ 15 ], soil trafficability and soil compaction [ 16 , 17 ], but also for hydrogeomorphological surveying to identify depth of boundaries between layers [ 7 ]. In our case it should indicate dense layers to detect the lakebed surface and the shallow sub-bottom strata in combination with the sediment echosounder.…”
Section: Methodsmentioning
confidence: 99%
“…Cone penetrometers are recommended in the American Society of Agricultural Engineers (ASAE) Standards as a standard method for measuring the penetrometer resistance PR of soils [ 14 ]. They are extensively used to evaluate soil strength especially in agriculture for resistance to root penetration [ 15 ], soil trafficability and soil compaction [ 16 , 17 ], but also for hydrogeomorphological surveying to identify depth of boundaries between layers [ 7 ]. In our case it should indicate dense layers to detect the lakebed surface and the shallow sub-bottom strata in combination with the sediment echosounder.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it provides a uniquely assembled robust system. Several researchers (Chung et al, 2003(Chung et al, , 2004a(Chung et al, , 2004b(Chung et al, , 2005Chung and Sudduth, 2003a, 2003bChukwu and Bowers, 2005;Topakci et al, 2010) focused on this approach and developed prototypes. Chung et al (2003) reported that although prototype sensors have been capable of providing on-the-go soil compaction data, they are all still in the development stages.…”
Section: Soil Compaction and Hard-panmentioning
confidence: 99%
“…The RS-232 serial communication protocol was used for two-way communication between the GPS receiver and the robot computer using the serial data cable of the GPS receiver. The GPS receiver installation data were sent to set up the GPS receiver via the server software [25].…”
Section: Remote Control Algorithmmentioning
confidence: 99%